The role of economic development and urban planning in the development of knowledge-based regions in secondary economic centres : a comparative study of Australia and Japan - Martinus, Kirsten R. (Curtin University, 2011)
Knowledge development and innovation have frequently been linked to rapid sustainable economic growth. Recent unprecedented globalisation and technological advancements have made understanding this relationship more important than ever. Indeed, innovation occurs through a complex process embedded in individual and collective human knowledge, experience and space, leading some to advocate the importance of fostering the social capital and creative capacity of local urban environments. This thesis hypothesises that urban planning and city design act as a framework for human interaction, movement and connectivity, influencing the efficiency of knowledge productivity and the innovation process.It contends that urban form impeding the interaction of soft infrastructure (social capital) is likely to require more government intervention and resources to overcome inefficiencies of low connectivity, accessibility and urban vibrancy. In contrast, urban form that enhances social capital tends to have better living and more accessible environments for all residents irrespective of socio-economic standing or aspiration. This thesis proposes that the high human attractiveness and movement of the latter improves the efficiency of knowledge exchange and innovation systems. Being the accumulative sum of all local systems, it is argued that a regional or national innovation system can be enhanced by local urban environments which better facilitate the flow of knowledge and innovation.This thesis presents the results of a four-year cross-national study exploring how urban form can leverage the socio-economic aspects of a city for new economy growth. It pays particular attention to the mechanisms linking new economy factors and the constructed urban environments in the case studies of Perth‟s Northwest Corridor in Western Australia, Australia, and Kansai Region in Japan. It identifies infrastructure types and the importance of urban form in generating an environment which facilitates knowledge development and innovation. This thesis contends that the environment of activity centres, for example train station developments, may be more supportive of national innovation and productivity priorities than others. Understanding how the urban space of such developments contributes to regional transfer mechanisms and flows can enable government policy to better identify and address regional innovation and knowledge gaps. Evidence presented suggests that urban planning not sensitive to the new economy contribution of urban space is likely to place unnecessary barriers in the innovation process.